A Study On The Policies And Procedures On Discretionary Trading Of Islamic Securities - Muhammad Affan Ahmad Nadzri; Aishath Muneeza (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2021)
Discretionary trading is an investment that a stockbroker executes using clients’ account which is done without getting specific approval from the client on decision whether to buy or sell the stock holding in the portfolio. The investment is conducted based on the experience and strategies made by the person in charge of the investment. The objective of this research is to study the existing policies and procedures of discretionary trading in the market, determine the shariah compliance of current practice of market discretionary trading, and formulate suitable shariah parameters for discretionary trading of Islamic securities. This research employs qualitative methodology. The finding related for this topic is limited as the researcher is the main findings. From the researcher findings, it is found that the respondents shared almost similar experience, but it is expressed in different ways. Besides, the priority of shariah compliant discretionary trading is highly important to the Muslim investors as it can be alternatives for them to grow their capital and the practice of discretionary trading in each stockbroker is different from the others due to the flexibility of the current guideline. It is anticipated that the findings of research will assist future researcher to develop and formulate better variables for Islamic discretionary trading.